Organ-specific expression and epigenetic traits of genes encoding digestive enzymes in the lance-leaf sundew (Drosera adelae). (28th November 2020) - Arai, Naoki; Ohno, Yusuke; Jumyo, Shinya; Hamaji, Yusuke; Ohyama, Takashi
Abstract: Over the last two decades, extensive studies have been performed at the molecular level to understand the evolution of carnivorous plants. As fruits, the repertoire of protein components in the digestive fluids of several carnivorous plants have gradually become clear. However, the quantitative aspects of these proteins and the expression mechanisms of the genes that encode them are still poorly understood. In this study, using the Australian sundew Drosera adelae, we identified and quantified the digestive fluid proteins. We examined the expression and methylation status of the genes corresponding to major hydrolytic enzymes in various organs; these included thaumatin-like protein, S-like RNase, cysteine protease, class I chitinase, β-1, 3-glucanase, and hevein-like protein. The genes encoding these proteins were exclusively expressed in the glandular tentacles. Furthermore, the promoters of the β-1, 3-glucanase and cysteine protease genes were demethylated only in the glandular tentacles, similar to the previously reported case of the S-like RNase gene da-I . This phenomenon correlated with high expression of the DNA demethylase DEMETER in the glandular tentacles, strongly suggesting that it performs glandular tentacle-specific demethylation of the genes. The current study strengthens and generalizes the relevance of epigenetics to trap organ-specific gene expression in D. adelae . We also suggest similarities between the trap organs of carnivorous plants and the roots of non-carnivorous plants. Abstract : Lance-leaf sundew provides an intriguing example of organ-specific DNA demethylation, which allows β-1, 3-glucanase, cysteine protease, and S-like RNase genes to be exclusively expressed in the glandular tentacles.